The New Map of Europe (1911-1914) : The Story of the Recent European Diplomatic Crises and Wars and of Europe's Present Catastrophe - Gibbons, Herbert Adams, 1880-1934 (Salt Lake City, UT : Project Gutenberg, 2017)
"The New Map of Europe (1911-1914)" by Herbert Adams Gibbons is a historical account written in the early 20th century. The book delves into the complex diplomatic crises and wars that reshaped Europe in the lead-up to World War I. Gibbons analyzes the geopolitical tensions involving major powers, particularly focusing on the impact of historical grievances and nationalistic fervor in regions like Alsace-Lorraine and the Balkans. The opening of the work introduces the author$1 (Bs experiences in Europe during a time of tumultuous change, detailing his observations on the sentiments of the people in Alsace-Lorraine after their annexation by Germany. Gibbons elaborates on the persistent unrest in the region, where strong French cultural and national identities clash with German nationalism amid ongoing persecution. The chapter sets the stage for an exploration of how these local tensions contribute to broader European conflicts, underscoring the intricate interplay of power, identity, and historical animosities that ultimately lead to a new geopolitical landscape in Europe. (This is an automatically generated summary.)s
Release date is 2017-01-31
Produced by Al Haines
Keywords: World War, 1914-1918 -- Causes; Eastern question (Balkan); Europe -- Politics and government -- 1871-1918; Competition, International